AAST multicenter prospective analysis of prehospital tourniquet use for extremity trauma. Issue 6 (18th June 2022) - Schroll, Rebecca; Smith, Alison; Alabaster, Kelsey; Schroeppel, Thomas J.; Stillman, Zachery E.; Teicher, Erik J.; Lita, Elena; Ferrada, Paula; Han, Jinfeng; Fullerton, Robert D.; McNickle, Allison G.; Fraser, Douglas R.; et al.
Abstract : Media summary: Large prospective multicenter study showed that prehospital tourniquets for major extremity trauma were associated with a threefold decreased incidence of arrival in shock without increased limb complications. #stopthebleed @BeccaSchroll @TraumaTulane. Abstract : BACKGROUND: Tourniquet use for extremity hemorrhage control has seen a recent increase in civilian usage. Previous retrospective studies demonstrated that tourniquets improve outcomes for major extremity trauma (MET). No prospective study has been conducted to date. The objective of this study was to evaluate outcomes in MET patients with prehospital tourniquet use. We hypothesized that prehospital tourniquet use in MET decreases the incidence of patients arriving to the trauma center in shock. METHODS: Data were collected prospectively for adult patients with MET at 26 Level I and 3 Level II trauma centers from 2015 to 2020. Limbs with tourniquets applied in the prehospital setting were included in the tourniquet group and limbs without prehospital tourniquets were enrolled in the control group. RESULTS: A total of 1, 392 injured limbs were enrolled with 1, 130 tourniquets, including 962 prehospital tourniquets. The control group consisted of 262 limbs without prehospital tourniquets and 88 with tourniquets placed upon hospital arrival. Prehospital improvised tourniquets were placed in 42 patients. Tourniquets effectively controlled bleeding in 87.7% of limbs. Tourniquet and control groups were similarly matched for demographics, Injury Severity Score, and prehospital vital signs ( p > 0.05). Despite higher limb injury severity, patients in the tourniquet group were less likely to arrive in shock compared with the control group (13.0% vs. 17.4%, p = 0.04). The incidence of limb complications was not significantly higher in the tourniquet group ( p > 0.05). CONCLUSION: This study is the first prospective analysis of prehospital tourniquet use for civilian extremity trauma. Prehospital tourniquet application was associated with decreased incidence of arrival in shock without increasing limb complications. We found widespread tourniquet use, high effectiveness, and a low number of improvised tourniquets. This study provides further evidence that tourniquets are being widely and safely adopted to improve outcomes in civilians with MET. LEVEL OF EVIDENCE: Therapeutic/Care Management; Level IV. Abstract :